Do Empty Beds Cause Cesarean Deliveries? - Florian Bachner; Martin Halla; Gerald J. Pruckner (Institute of Labor Economics (IZA), 2024)
We examine how the number of beds available in a maternity ward affects the likelihood of cesarean delivery and maternal health. Our analysis is based on administrative data from Austria. We exploit idiosyncratic daily variation in the occupancy of maternity hospital beds. We find that empty beds increase the probability of cesarean delivery, hospitalization, and readmission. A one standard deviation decrease in maternity bed occupancy increases the probability of cesarean delivery by 4.0% and subsequent hospitalization by 5.8%. Expectant mothers may benefit from a crowded hospital, even at unfavorable patient-staff ratios, because it may lead to less harmful overtreatment.
Keywords: I12; J13; J11; J22; J21; 330; capacity; hospital crowding; supplier-induced demand; cesarean delivery; cesarean section; overtreatment; maternal health